Role of project planning and project manager competencies on public sector project success - Muhammad Irfan; Khan, Sanam Zaib; Hassan, Nasruddin; Hassan, Mazlan; Habib, Muhammad; Khan, Salma; Khan, Hadi Hassan (MDPI AG, 2021)
Even though the world has progressed exponentially, the core reasons for the failure of many public sector projects remain the same, i.e., the poor planning and competency of a project manager. Therefore, it becomes essential even in the contemporary world to assess and evaluate a model that determines the effect of planning and the project manager’s competency on the success of public sector projects. Moreover, the present study aims to assess the role of project planning and the project manager’s competency in project success in the context of project management methodology defined by the Project Management Institute. In the current survey-based study, a sample of 260 project engineers, from the public sector organizations operating in Balochistan, that were engaged in projects was taken in order to understand the relationship between the constructs. Quantitative data were collected to address the proposed hypotheses using the partial least squares structural equation modeling technique. It was inferred from the findings that planning and competency have a significant positive impact on the success of public sector projects. Among the two, it was determined that planning for public sector projects has a greater role in the success of projects. Therefore, it is concluded based on the results of the study that in future, due consideration should be given to planning and the abilities of a project manager.